The ICT and Innovative Integration of Primary Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
To effectively aid primary schools - both their administrators and educators - in leveraging ICT for enhanced student learning, it's crucial to grasp what defines a primary school in our modern era. Hence, our initial investigation sought to understand the integration of ICT in our selected schools: its inception, evolution, and the insights gained from their experiences. We aimed to explore how ICT is managed within these schools concerning classroom setup, computer accessibility, home-school connections, and their evolving needs amidst technological advancements.